Factors Affecting Online Donation Intention in Donation-based Crowdfunding - Irantha Hendrika Kenang; Gladys Gosal (Bina Nusantara University, 2021)
The research aimed to determine factors affecting online donation intention of Generation Y, particularly in donation-based crowdfunding in Indonesia. Applying a quantitative method, the research used a combination of Theory of Planned Behavior (Attitude, Subjective Norms, Perceived Behavioral Control), Social Presence Theory, and S-O-R Theory (Website Quality, Transaction Convenience, Perceived Credibility). The research used purposive sampling with total of 118 respondents. The result of the analysis suggests that millennials’ intention to donate is significantly affected by the perceived credibility of the crowdfunding platform. This is mainly due to online transaction, hence the donors are concerned about whether their donation is going to be distributed properly. Subsequently, the perceived credibility of crowdfunding platform is significantly affected by social presence, website quality, and transaction convenience, which support previous research related to Social Presence Theory and S-O-R Theory. Meanwhile, attitude, subjective norms, and perceived behavioral control have no significant impact on intention to donate, which may be due to several issues such as trust and security issues considering the donation is conducted through online. The crowdfunding platforms and fundraisers in Indonesia are expected to have guidelines about important aspects that may affect individual’s intention to donate in crowdfunding platform.